Main structural and topological characteristics of computer network - Кулаков, Ю. О.; Малік, Абу-А’ра Махмуд; Нагорний, Л. Я. (Proceedings of National Aviation University (archive), 1999)
Considered here are the main topological characteristics of graphs and their use in analyzing and synthesizing modern computer networks. Substantiated is the importance of such parameters as structural proximity of elements, network diameter, root-mean-square deflection of vertexes in analysis of network topologies. Here we show how it is possible to use these parameters at the stages of synthesis and analysis of corporate networks. Considered is the algorithm of network structure decomposition under different intensity of information flows. Compared are the values of the main topological characteristics of homogeneous structures under different number of vertexes